Risk factors for early neonatal sepsis in Hospital Hermilio Valdizán Medrano. Huánuco, Perú. 2016 - Falcón-Fabian, Melchor (2019)
Objective: To determine the main risk factors associated with early probable neonatal sepsis. Methodology: An observational, analytical, retrospective study of cases and controls was carried out. The cases were 71 newborns diagnosed with probable early sepsis associated with one or more of the factors under study; and the control group: 71 neonates without early probable neonatal sepsis with one or more of the factors under study, the data were collected from the medical records. The bivariate analysis of the evaluated risk factors, low birth weight, infection of the maternal urinary tract in the third trimester and premature membrane rupture, was carried out through the Chi-2 test, Odds ratio with a level of confidence to 95%. For the comparative analysis of the quantitative variables, the man whitney U test was used. Results: In the bivariate analysis, maternal urinary tract infection was identified as risk factors (OR = 2.515, 95% CI = 1.246 - 5.075, p = 0.00), low birth weight (OR = 3.5, 95% CI = 1.65-7.84, p = 0.01), the premature rupture of membranes was not statistically significant (OR = 0.7, 95% CI = 0.31-1.7) Conclusions: Urinary tract infection and low birth weight were the most important risk factors in this study for the development of early probable neonatal sepsis.